The Prophylactic Effect of Pinocembrin Against Doxorubicin-Induced Cardiotoxicity in an In Vitro H9c2 Cell Model - Sangweni, Nonhlakanipho F.; Moremane, Malebogo; Riedel, Sylvia; van Vuuren, Derick; Huisamen, Barbara; Mabasa, Lawrence; Barry, Reenen; Johnson, Rabia (Frontiers in Pharmacology, 2020)
Background The clinical use of Doxorubicin (Dox) is significantly limited by its dose-dependent cardiotoxic side effect. Accumulative evidence suggests that the use of flavonoids, such as the antioxidative Pinocembrin (Pin), could be effective in the prevention of Dox-induced cardiotoxicity. Accordingly, we investigated the ability of pinocembrin (Pin) to attenuate Dox-induced cardiotoxicity in an in vitro H9c2 cardiomyoblast model. Methodology The cardioprotective potential of Pin was established in H9c2 cells. Here, cells were treated with Dox (2μM), Dox (2μM) + Pin (1μM), and Dox (2μM) + Dexrazoxane (20μM) for 6 days. Thereafter, the safe co-administration of Pin with Dox, in a cancer environment, was investigated in MCF-7 breast cancer cells subjected to the same experimental conditions. Untreated cells served as the control. Subsequently, Pin’s ability to attenuate Dox-mediated oxidative stress, impaired mitochondrial bioenergetics and potential, as well as aggravated apoptosis was quantified using biochemical assays. Results The results demonstrated that co-treatment with Pin mitigates Dox-induced oxidative stress by alleviating the antioxidant enzyme activity of the H9c2 cells. Pin further reduced the rate of apoptosis and necrosis inferred by Dox by improving mitochondrial bioenergetics. Interestingly, Pin did not decrease the efficacy of Dox but, rather increased the rate of apoptosis and necrosis in Dox-treated MCF-7 cells. Conclusion The findings presented in this study showed, for the first time, that Pin attenuates Dox-induced cardiotoxicity without reducing its chemotherapeutic effect. We propose that additional studies, using in vivo models, should be conducted to further investigate Pin as a suitable candidate in the prevention of the cardiovascular dysfunction inferred by Dox administration.